Intracellular trafficking of Notch orchestrates temporal dynamics of Notch activity in the fly brain - Miaoxing Wang; Xujun Han; Chuyan Liu; Rie Takayama; Tetsuo Yasugi; Shin-Ichiro Ei; Masaharu Nagayama; Yoshitaro Tanaka; Makoto Sato (Nature Communications, 2021)
During Drosophila development, two peaks of Notch activity propagate across the neuroepithelium to generate neuroblasts. Here, the authors show Notch cis-inhibition under the control of intracellular Notch trafficking establishes these two peaks, which temporally control neurogenesis in the brain.